1986
DOI: 10.1002/ejsp.2420160403
|View full text |Cite
|
Sign up to set email alerts
|

Distinctiveness and the salience of social category memberships: Is there an automatic perceptual bias towards novelty?

Abstract: It was hypothesized that the effects of novelty on social category membership salience may be mediated by perceivers' current tasks, rather than by an automatic perceptual bias

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
1
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(70 citation statements)
references
References 30 publications
4
64
1
1
Order By: Relevance
“…As mentioned in the introduction, research has found that diverse interpersonal contexts lead to an increase in category accessibility and stereotyping (e.g. McGuire et al, 1978;Oakes & Turner, 1986;Stroessner, 1996;Zarate & Smith, 1990). In contrast, the present research found that such contexts have the opposite effect on implicit prejudice.…”
Section: Implications and Future Directionscontrasting
confidence: 63%
See 1 more Smart Citation
“…As mentioned in the introduction, research has found that diverse interpersonal contexts lead to an increase in category accessibility and stereotyping (e.g. McGuire et al, 1978;Oakes & Turner, 1986;Stroessner, 1996;Zarate & Smith, 1990). In contrast, the present research found that such contexts have the opposite effect on implicit prejudice.…”
Section: Implications and Future Directionscontrasting
confidence: 63%
“…In fact, research on category activation and explicit stereotyping has shown primarily contrast effects in interpersonal contexts (e.g. McGuire et al, 1978;Oakes & Turner, 1986;Stroessner, 1996;Zarate & Smith, 1990). It is worth noting that the research described above demonstrating assimilation of implicit prejudice to context relied solely on presentations of person targets in front of environmental background contexts.…”
Section: Introductionmentioning
confidence: 97%
“…Variations in the salience of personal versus group self-categorizations can have marked effects on attitudes and behaviour (Oakes and Turner, 1986;Oakes, Turner and Haslam, 1991;Turner et al, 1987). However, the specific conditions under which personal or group self-identities become salient and the interrelationship between these determinants remains unclear Hogg and McGarty, 1990).…”
Section: Self-categorization Theory (Sct)mentioning
confidence: 99%
“…However, the specific conditions under which personal or group self-identities become salient and the interrelationship between these determinants remains unclear Hogg and McGarty, 1990). A number of factors have, nevertheless, been proposed to be important to the accentuation of specific self-concepts (Brown and Turner, 1981;Dion Earn and Yee, 1978;Fiske and Taylor, 1984;Hogg and Turner, 1987;Oakes and Turner, 1986;Turner et al, 1987;Zander, Stotland and Wolfe, 1960). For example, some factors which influence the salience of group identity are: (a) When goals or task orientations are group-related, (b) when groups are accentuated and social entitativity is enhanced, (c) when separation and clarity between groups are accentuated so that the perceived similarity and differences between individuals are correlated with division into group membership, (d) in intergroup competition and conflict situations, (e) when explicit references to group identity are made, and/or (f) when group membership is cognitively accessible.…”
Section: Self-categorization Theory (Sct)mentioning
confidence: 99%
“…However, this generalization process is most likely when group membership is made salient (Vivian et al 1997), such as by the prototypicality of the outgroup members (Oakes and Turner 1986;Oakes et al 1991). For example, Brown et al (1999) showed that positive attitudinal generalization was facilitated by encounters with prototypical outgroup members.…”
Section: Representative Prototypicalitymentioning
confidence: 99%